(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the development of speech and communication culture in future teachers within a digital educational environment from pedagogical, didactic, and methodological perspectives. Today, the widespread use of electronic platforms, distance learning tools, multimedia resources, video conferencing services, and interactive tasks in the higher education system requires future educators to possess not only profound knowledge of the subject content but also effective communication in the digital space, fluent expression of thought, adherence to professional ethical standards, and the choice of the correct speech strategy in various communicative situations.